A review of heat and mass transfer improvement techniques for dehumidifiers and regenerators of liquid desiccant cooling systems. (5th November 2019) - Ren, Haoshan; Ma, Zhenjun; Liu, Jingjing; Gong, Xuemei; Li, Weihua
Highlights: Heat and mass transfer improvement techniques are reviewed. In-depth investigations on the design of packing materials are needed. Using inserts in fluid channels is effective but needs to be optimally designed. Effective and durable solutions for membrane deflection are needed. Abstract: Liquid desiccant cooling is being considered as an alternative to vapour compression air conditioning systems and has been extensively investigated in recent decades. The dehumidifiers and regenerators are the key components of liquid desiccant cooling systems and their heat and mass transfer performance significantly influences the performance of liquid desiccant cooling systems. This paper provides an overview of heat and mass transfer improvement techniques used to enhance the performance of direct-contact and indirect-contact dehumidifiers and regenerators used in liquid desiccant cooling systems. A number of techniques such as using a third heat transfer fluid, selection of packing materials, and tube arrangement, were reviewed and the performance of the dehumidifiers and regenerators using such techniques was summarised. The results showed that a large number of heat and mass transfer improvement techniques have been developed and used to enhance the performance of dehumidifiers and regenerators while further investigations on additives in liquid desiccants and surface modifications for direct-contact dehumidifiers and regenerators, and membrane deflection of indirect-contact dehumidifiers and regenerators might be still needed. In the meanwhile, design optimisation of packing materials (e.g. geometrical parameters) and fins with complex geometries for direct-contact dehumidifiers and regenerators, and inserts for indirect-contact dehumidifiers and regenerators may further improve their heat and mass transfer performance.